Religious figures in controversial advertisements (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
In the contemporary world, traditional forms of advertising seem to be losing impact. In the advertising clutter, ad makers try to make their advertisements stand out by the implementation of new and attractive strategies. Shockvertising is one of them. This unconventional approach to advertising aims at astonishing its audience by presenting shocking and controversial content. It is based on the assumption that arousing strong emotions will enhance the process of memorising. Additionally, the provocative nature of the message is intended to shock, and thus generate publicity, which in turn increases brand awareness, and consequently influences sales. The main aim of this questionnaire-based research was to verify what kind of feelings and emotions are evoked among recipients of iconoclastic images in advertisements for different products and to check if the audience feels encouraged and convinced by such an appeal. Moreover, in the cultural dimension, the study aimed at assessing the sensitivity to controversial topics including religious concepts. The audience was exposed to images of religious characters combined with profane or taboo topics and asked for opinions. Based on the results, it can be concluded that, from a cultural point of view, the Polish audience demonstrates sensitivity to religious issues. Besides, from a marketing perspective, although shockvertising proves effective in distinguishing the brand, on a conscious level, it fails to influence the actual purchase behaviour.